Co monatomic modified alpha-Fe2O3 nanorod photo-anode as well as preparation method and application thereof

By modifying the Co single-atom catalyst on the surface of α-Fe2O3 nanocolumns and sintering with methane premix flame, Co SACs/α-Fe2O3 photoanode is formed, the problem of low efficiency in the ammonia oxidation reaction is solved, and efficient photoelectrocatalytic ammonia oxidation and energy-efficient application of ammonia oxidation is achieved.

CN119724940APending Publication Date: 2025-03-28ZHONGBEI SUNAC (XIAMEN) TECHNOLOGY TRANSFER CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411910218.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing α-Fe2O3 photoanodes have problems such as poor conductivity, short life of photogenerated carriers, and serious surface photogenerated electrons and hole recombination in ammonia oxidation reaction, resulting in low catalytic efficiency.

Method used

Co SACs/α-Fe2O3 photoanode was formed by modifying the Co single atom catalyst on the surface of the α-Fe2O3 nanocolumn and sintering in ultra-high temperature using a methane premix flame. This method improves the separation efficiency of photogenerated carriers and the adsorption activity of ammonia molecules by introducing Co single atom catalyst.

Benefits of technology

The efficiency of photoelectro-catalyzed ammonia oxidation reaction was significantly improved, with the ammonia oxidation rate reaching 53%, and the energy-based application of ammonia was realized, with the Faraday efficiency of hydrogen production reaching 23.93%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724940A_ABST
    Figure CN119724940A_ABST
Patent Text Reader

Abstract

The invention discloses a Co monatomic modified alpha-Fe2O3 nanorod photo-anode and a preparation method and application thereof.The preparation method comprises the steps that during preparation, fluorine-doped SnO2 (FTO) conductive glass serves as a matrix, and an alpha-Fe2O3 nanorod precursor is prepared through a hydrothermal synthesis method; the preparation method comprises the following steps: taking Co (NO3) 2.6 H2O, Zn (NO3) 2.6 H2O and 2-methylimidazole as main raw materials, and preparing a Co monatomic catalyst by adopting a normal-temperature chemical method; then, the Co monatomic catalyst and the precursor alpha-Fe2O3 are rapidly sintered in ultra-high-temperature flame by using methane premixed flame. The Co monatomic catalyst is modified on the surface of the alpha-Fe2O3 nanorod, so that on one hand, the compounding of photo-induced electrons and holes is inhibited, and the charge transfer efficiency in the electrode and the charge transfer efficiency at a solid-liquid interface are improved; on the other hand, the Co SACs are used as active sites of the ammoxidation reaction, and photoelectrocatalysis ammonia decomposition is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ammonia oxidation photoanode materials, and in particular to a Co single atom modified alpha-Fe2O3 nanocolumn photoanode and a preparation method and application thereof. Background Art

[0002] Ammonia (NH3) is a widely used chemical product with huge output. It is also considered an ideal hydrogen storage carrier because of its high hydrogen content per unit density, mild storage and transportation conditions, and mature industrial application infrastructure. Photoelectrocatalytic ammonia oxidation hydrogen production is a new type of green hydrogen production technology using ammonia as raw material and solar energy as drive. Using efficient ammonia oxidation photoanode materials, using thermodynamically favorable photoelectrocatalytic ammonia oxidation reaction (oxidation potential 0.06V RHE ) replaces the slow photoelectrocatalytic water oxidation reaction (oxidation potential 1.23V RHE ), and combined with the cathode hydrogen evolution reaction, theoretically, it can save 95% of the energy consumption for hydrogen production, providing an efficient and energy-saving method for realizing the conversion of solar energy to hydrogen energy. At the same time, the photoelectrocatalytic ammonia oxidation reaction does not require the introduction of hypochlorite as a mediating substance, and can achieve clean and harmless "ammonia-hydrogen" conversion. In addition, highly active and highly stable ammonia oxidation photoelectrocatalytic materials are also crucial for the design of room-temperature ammonia fuel cells and the development of ammonia nitrogen wastewater remediation technology.

[0003] Hematite (α-Fe2O3) is a typical n-type semiconductor with an appropriate band gap (about 2.1eV) and can absorb a wide visible light part of the solar spectrum. In addition, hematite is abundant on the earth, the raw materials are cheap, and the economy is good. It has good chemical stability and is not easily corroded during the experiment. The processing and preparation methods are mature and easy to prepare, such as hydrothermal method and electrochemical deposition method. Therefore, α-Fe2O3 has become one of the promising photoanode materials. Yuchao Zhang et al. found that α-Fe2O3 photoanode can achieve efficient and stable catalytic ammonia oxidation reaction (current efficiency>80%) in aqueous solution through a non-radical nucleophilic adsorption mechanism, which significantly improves the total photocurrent and cathode hydrogen evolution rate.

[0004] However, hematite has the disadvantages of poor conductivity, short lifetime of photogenerated carriers, serious recombination of surface photogenerated electrons and holes, low electron mobility, and few surface active sites. Co-catalyst modification is one of the main strategies to improve the photoelectrocatalytic performance of α-Fe2O3. By introducing other semiconductor materials to form a heterojunction, the separation of photogenerated electrons and holes is promoted and their recombination is inhibited; at the same time, co-catalyst materials are usually easier to bind to ammonia molecules and act as surface active sites in ammonia oxidation reactions. ChengkaiXia et al. combined the FePO4 co-catalyst covering layer on the surface of α-Fe2O3 and applied it to the study of photoelectrochemical ammonia decomposition: after the FePO4 co-catalyst covering layer was electrochemically activated, the FePi covering layer was converted into FeOOH, and the activated covering layer provided a large number of active sites for the ammonia adsorption process, thereby improving the kinetic properties of the photoanode material in the ammonia oxidation reaction, and achieved an ammonia degradation rate of about 40% within 3 hours. Lei Wu et al. modified the Cu-BiVO4 complex on the surface of BiVO4 photoanode, which promoted the adsorption of ammonia molecules on the photoanode surface, improved the charge separation efficiency on the BiVO4 photoanode surface, and achieved efficient photoelectrocatalytic ammonia oxidation.

[0005] Currently, modifying the co-catalyst on the surface of transition metal oxide photoanode to promote the adsorption and desorption of ammonia molecules on the photoanode surface, thereby inhibiting the water oxidation reaction that competes with ammonia oxidation, is considered to be a necessary strategy to achieve efficient photoelectrocatalytic ammonia decomposition. Summary of the invention

[0006] The purpose of the present invention is to provide a Co single atom modified α-Fe2O3 nanocolumn photoanode and a preparation method and application thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a Co single atom modified α-Fe2O3 nanocolumn photoanode comprises the following steps:

[0009] S1, preparation of α-Fe2O3 nanorod precursor by hydrothermal synthesis;

[0010] With fluorine-doped SnO2 (FTO) conductive glass as the matrix, FeCl3·6H2O, CO(NH)2 and HCl were dissolved in deionized water, and the precursor α-Fe2O3 nanorods were synthesized on FTO conductive glass by a hydrothermal method.

[0011] S2, preparation of Co single atom catalyst by room temperature chemical method;

[0012] Co(NO3)2·6H2O, Zn(NO3)2·6H2O and 2-methylimidazole were dissolved in methanol to obtain a Co-based metal organic framework material, which was then calcined in an argon atmosphere to obtain a Co single atom catalyst.

[0013] S3, Co SACs / α-Fe2O3 photoanode prepared by methane premixed flame sintering.

[0014] Using a methane premixed flame, the Co single atom catalyst and the precursor α-Fe2O3 are rapidly sintered in an ultra-high temperature flame.

[0015] Furthermore, the step S1 specifically includes the following steps:

[0016] S1.1 Cut the FTO glass, clean it with ultrasonic, and dry it;

[0017] S1.2 remove the residual organic protective layer on the surface of FTO glass;

[0018] S1.3 Weigh 0.81 g of FeCl3·6H2O and 0.27 g of CON2H4 and dissolve them in 30 mL of deionized water to prepare a mixed solution, and adjust the pH to 1.5 with concentrated hydrochloric acid;

[0019] S1.4 Cover the non-conductive surface of the cleaned FTO glass with polyimide tape, fix it in a hydrothermal kettle, pour the above mixed solution into it to immerse it, seal it, and place it in a hydrothermal reaction at 110°C for 6 hours;

[0020] S1.5 After the hydrothermal reaction is completed, the FTO conductive glass is taken out and cleaned with deionized water, then placed in a muffle furnace, annealed at 550°C for 1h, and cooled to room temperature with the furnace to obtain a deep red α-Fe2O3 precursor.

[0021] Furthermore, the step S2 specifically includes the following steps:

[0022] S2.1 Weigh 43.65 mg of cobalt nitrate and 847.84 mg of zinc nitrate and dissolve them in 40 mL of methanol to prepare solution A;

[0023] S2.2 Weigh 2 g of 2-methylimidazole and dissolve it in 20 mL of methanol to prepare solution B;

[0024] S2.3 While stirring solution A at a speed of 1000 rpm, quickly pour solution B into solution A, making sure that solution B does not touch the bottle wall, to obtain a mixed solution;

[0025] S2.4 Stir the mixture for 2 seconds, centrifuge and collect the precipitate;

[0026] S2.5 The precipitate was washed three times with methanol and then dried thoroughly in a drying oven at 60 °C to obtain a Co MOF precursor;

[0027] S2.6 The obtained Co MOF precursor is placed in a tubular furnace and annealed in an argon atmosphere by heating to 900°C for 4h 30min and then keeping the temperature for 2h. After the end of the heat preservation, it is naturally cooled to room temperature to obtain Co SACs.

[0028] Furthermore, the step S3 specifically includes the following steps:

[0029] S3.1 Mix 10 mg Co SACs, 7.6 mL deionized water, 2.4 mL isopropanol, and 20 uL Nafion solution to prepare a suspension;

[0030] S3.2 Place the suspension in ice water for 5 min and then disperse it ultrasonically for 20 min;

[0031] S3.3 Place the α-Fe2O3 nanocolumn precursor horizontally on a tray, add 100uL of the suspension, dry at 70℃ for 15min, wash with deionized water, and blow dry with nitrogen;

[0032] S3.4 Repeat the drip coating and drying process 10 times;

[0033] S3.5 uses a McKenna burner, with the flow rates of CH4 and air set at 2.22 and 17.58 SLPM, and the fuel-to-oxygen equivalence ratio at 1.2;

[0034] S3.6 The α-Fe2O3 nanocolumn precursor coated with Co SACs was rapidly annealed in an oxygen-deficient flame zone at 1000°C for 30s to finally obtain the Co SACs / α-Fe2O3 photoanode.

[0035] The present invention also provides a Co single atom modified α-Fe2O3 nanocolumn photoanode, which is a CoSACs / α-Fe2O3 composite structure and presents a nanocolumn structure with a few clusters gathered at the top of the nanocolumn. In the Co SACs, Co atoms with relatively large atomic mass are irregularly dispersed inside the clusters, showing typical single atom catalyst structural characteristics.

[0036] The Co single atom modified α-Fe2O3 nanocolumn photoanode described in the present invention can be applied to photoelectrocatalytic ammonia oxidation and ammonia nitrogen pollutant degradation.

[0037] The present invention uses a methane premixed flame for the first time to rapidly sinter the Co single atom catalyst and the precursor α-Fe2O3 in an ultra-high temperature flame. Through the instantaneous high temperature environment and reducing atmosphere provided by the methane premixed flame, a large number of oxygen vacancies are introduced into the α-Fe2O3 precursor while the Co single atom is tightly combined with the α-Fe2O3. By modifying the Co single atom catalyst on the surface of the α-Fe2O3 nanocolumn, on the one hand, the recombination of photogenerated electrons and holes is suppressed, and the charge transfer efficiency inside the electrode and the charge transfer efficiency at the solid-liquid interface are improved; on the other hand, Co SACs, as active sites for ammonia oxidation reactions, realize photoelectrocatalytic ammonia decomposition, decomposing ammonia (NH3) in aqueous solution into nitrate and hydrogen (H2), and realizing the energy application of ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0039] Figure 1 The reducing methane premixed flame produced by the McKenna burner.

[0040] Figure 2 The morphology characterization results of Co SACs / α-Fe2O3 photoanode;

[0041] In the figures: (a) SEM image of Co SACs / α-Fe2O3 photoanode; (b) TEM image of Co SACs; (c) TEM image of Co SACs / α-Fe2O3; (d) EDS spectrum of Co SACs / α-Fe2O3.

[0042] Figure 3 The morphology and composition characterization results of Co SACs / α-Fe2O3 photoanode;

[0043] In the figure: (a) XRD spectra of FTO conductive glass and Co SACs / α-Fe2O3 photoanode; (b) XRD spectra of Co SACs and Co MOF powder; (c) XPS spectra of Co SACs and Co MOF powder.

[0044] Figure 4 Cyclic voltammetry (CV) curve of Co SACs / α-Fe2O3 photoanode in 0.1 mol / L KOH solution;

[0045] In the figure: (a) α-Fe2O3 photoanode; (b) cyclic voltammetry curves of Co SACs / α-Fe2O3 photoanode before and after adding 500 ppm NH3·H2O in 0.1 mol / L KOH solution.

[0046] Figure 5 The photoelectrocatalytic ammonia decomposition test results of Co SACs / α-Fe2O3 photoanode;

[0047] Figure: (a) Time-current curve of Co SACs / α-Fe2O3 photoanode after adding 500ppm NH3·H2O in 0.1mol / L KOH solution; (b) NO3 in the solution before and after the time-current test - UV-visible absorption spectrum; (cd) UV-visible absorption spectrum of NH4+ in solution and fitted NH3 oxidation rate during time-current test; (ef) Gas chromatography of gas in the reactor and fitting results during time-current test. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0049] Example 1

[0050] Preparation of Co SACs / α-Fe2O3 photoanode

[0051] S1, preparation of α-Fe2O3 nanorod precursor by hydrothermal synthesis;

[0052] 1) Cut the FTO glass with a thickness of 2.2 mm into small pieces with a size of 1.5 cm*2 cm, immerse them in acetone, ethanol, and deionized water for ultrasonic cleaning in turn, and then dry the cleaned FTO glass.

[0053] 2) The dried FTO glass was cleaned with an ultraviolet ozone cleaning machine and activated with ozone at 150° C. for 30 minutes to remove the residual organic protective layer on the surface of the FTO glass.

[0054] 3) Weigh 0.81 g of FeCl3·6H2O and 0.27 g of CON2H4 and dissolve them in 30 mL of deionized water to prepare a mixed solution, and adjust the pH value to 1.5 with concentrated hydrochloric acid to obtain a mixed solution;

[0055] 4) The cleaned FTO glass was taped with polyimide tape and fixed in a hydrothermal reactor, and the mixed solution was poured into it to immerse it. After sealing, the hydrothermal reactor was placed at 110° C. for hydrothermal reaction for 6 hours to obtain FeOOH nanocolumns;

[0056] 5) After the hydrothermal reaction is completed, the FTO conductive glass is taken out and cleaned with deionized water, then placed in a muffle furnace, annealed at 550°C for 1h, and cooled to room temperature with the furnace to obtain a deep red α-Fe2O3 precursor.

[0057] S2, preparation of Co single atom catalyst by room temperature chemical method;

[0058] 1) Weigh 43.65 mg of cobalt nitrate and 847.84 mg of zinc nitrate and dissolve them in 40 mL of methanol to prepare solution A;

[0059] 2) Weigh 2 g of 2-methylimidazole and dissolve it in 20 mL of methanol to prepare solution B;

[0060] 3) While stirring solution A at 1000 rpm, quickly pour solution B into solution A, being careful to ensure that solution B does not touch the bottle wall;

[0061] 4) The mixture was stirred for 2 h, and the precipitate was collected by centrifugation (centrifuge speed 6000 rpm);

[0062] 5) The precipitate was washed three times with methanol and then dried thoroughly in a drying oven at 60° C. to obtain a Co MOF precursor.

[0063] 6) The obtained Co MOF precursor was placed in a tubular furnace and annealed in an argon atmosphere with an argon flow rate of 5 SCCM. The temperature was raised to 900° C. for 4 h 30 min and then kept at this temperature for 2 h. After the end of the heat preservation, it was naturally cooled to room temperature to obtain Co SACs.

[0064] Preparation of Co SACs / α-Fe2O3 photoanode by premixed flame sintering of S3 and methane

[0065] 1) Mix 10 mg Co SACs, 7.6 mL deionized water, 2.4 mL isopropanol and 20 uL Nafion solution to prepare a suspension.

[0066] 2) Place the suspension in ice water for 5 minutes and disperse it in an ultrasonic cleaner for 20 minutes.

[0067] 3) Place the α-Fe2O3 nanocolumn precursor horizontally on a tray, add 100uL of the suspension, dry it in a drying oven at 70°C for 15 minutes, gently wash it with deionized water, and then purge it with nitrogen to remove the remaining moisture;

[0068] 4) Repeat the drip coating and drying process 10 times.

[0069] 5) Use a McKenna burner (such as Figure 1As shown), the flow rates of CH4 and air were set to 2.22 and 17.58 SLPM, and the fuel to oxygen equivalence ratio (Φ) was 1.2.

[0070] 6) The α-Fe2O3 nanorod precursor coated with Co SACs was rapidly annealed in an oxygen-deficient flame at 1000°C for 30s to finally obtain a Co SACs / α-Fe2O3 photoanode.

[0071] In this embodiment, the chemical reagents used were all analytically pure, and the experimental water was all deionized water with a resistivity of 18 MΩ·cm.

[0072] Figure 2 (a) is a scanning electron microscopy (SEM) image of the Co SACs / α-Fe2O3 photoanode. As can be seen from the figure, the Co SACs / α-Fe2O3 composite structure after methane premixed flame treatment presents a nanopillar structure, with a few clusters gathered at the top of the nanopillar. Figure 2 (b) is the transmission electron microscopy (TEM) image of Co SACs. It can be seen that in Co SACs, Co atoms with larger relative atomic mass are irregularly dispersed inside the clusters, showing typical single-atom catalyst structural characteristics. Figure 2 (c) and Figure 2 (d) TEM image and EDS spectrum of Co SACs / α-Fe2O3 photoanode, which shows that Co SACs and α-Fe2O3 are tightly bound.

[0073] Figure 3 (a) is the XRD spectrum of FTO conductive glass and Co SACs / α-Fe2O3 photoanode. In the XRD spectrum of Co SACs / α-Fe2O3 photoanode, the diffraction peaks at 33.15°, 35.61°, and 63.98° correspond to the (104), (110), and (300) crystal planes in the standard PDF card of α-Fe2O3 (JCPDno.33-0664). This indicates that α-Fe2O3 was successfully synthesized on FTO glass, and CoSACs could not be detected due to its low content. The XRD spectra of Co SACs and Co MOF precursors are shown in Figure 1. Figure 3 As shown in (b), Co SACs do not have a crystalline morphology, so there is no obvious diffraction peak in the spectrum. The XPS test of Co SACs can confirm the exact existence of the Co element.

[0074] Example 2

[0075] Application of Co SACs / α-Fe2O3 photoanode in photoelectrocatalytic ammonia oxidation

[0076] The cyclic voltammetry (CV) curves of the Co SACs / α-Fe2O3 photoanode grown in 0.1 mol / L KOH solution were tested, with the scanning potential range of 0.4 V to 1.7 V. RHE , the scanning rate is 10mV / s. Figure 4 As shown in Figure 2, after adding 500 ppm of NH3·H2O, the current density of the cyclic voltammetry curve of the Co SACs / α-Fe2O3 photoanode increased significantly and reached 1.6 V. RHE As a control, when the α-Fe2O3 photoanode was used for the same test, there was no significant difference in the current density before and after the addition of NH3·H2O. It can be seen that the Co SACs / α-Fe2O3 photoanode prepared in the present invention can be used for photoelectrocatalytic ammonia decomposition.

[0077] Using Co SACs / α-Fe2O3 photoanode as the working electrode and platinum electrode as the cathode, the time-current curve of Co SACs / α-Fe2O3 photoanode was tested under a two-electrode system with a potential difference of 1.6V. The test was carried out in a completely airtight photoelectrocatalytic reactor. The cathode and anode reaction cells each had a catheter directly connected to the gas chromatograph. The gas chromatograph was used to collect gas substances in the reactor in situ every 10 minutes and calculate the gas production. At the same time, 100μL of electrolyte in the reaction cell was collected every 10 minutes, and the liquid phase product composition information was detected using a liquid chromatograph. The test results of the photoelectrocatalytic ammonia decomposition of Co SACs / α-Fe2O3 photoanode are shown in the figure. Figure 5 As shown. Figure 5 (a) It can be seen that the Co SACs / α-Fe2O3 photoanode works stably within 2 hours of the test. Liquid chromatography test and fitting curve are shown in Figure 5 (bd) shows that after 2 hours, about 53% of the NH3 in the solution was oxidized, and the oxidized NH3 in the solution was converted into NO3 - In the control group using α-Fe2O3 photoanode, the NH3 oxidation rate was close to the natural oxidation rate of NH3 (10% / 2h). The results of gas chromatography analysis showed that during the reaction, no nitrogen and oxygen were generated at the photoanode, hydrogen was generated at the cathode, and the Faraday efficiency of NH3-H2 conversion was 23.93%.

[0078] In summary, the present invention uses a methane premixed flame to sinter an α-Fe2O3 nanocolumn precursor with a Co single atom catalyst at ultra-high temperature to prepare a Co SACs / α-Fe2O3 photoanode with photoelectrocatalytic ammonia oxidation activity. Since the Co single atom catalyst provides active sites for the adsorption of NH3 molecules, the adsorption efficiency of NH3 molecules in the photoelectrochemical reaction in the ammonia solution is higher than the competitive water molecule adsorption process, so that the ammonia oxidation reaction has a major influence in the photoelectrochemical reaction. In actual tests, the oxidation rate of ammonia molecules by Co SACs / α-Fe2O3 photoanode reached 53% within 2 hours, and NH3 molecules were converted into H2 and NO3 - ions, the Faraday efficiency of hydrogen production of Co SACs / α-Fe2O3 photoanode reached 23.93%. The above implementation cases show that the prepared Co SACs / α-Fe2O3 photoanode can be used for photoelectrocatalytic ammonia oxidation to produce hydrogen and ammonia nitrogen pollutant degradation.

[0079] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode, characterized in that: The steps include: S1, preparation of α-Fe2O3 nanorod precursor by hydrothermal synthesis; S2, preparation of Co single atom catalyst by room temperature chemical method; S3, Co SACs / α-Fe2O3 photoanode prepared by methane premixed flame sintering.

2. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 1, characterized in that: In the step S1, fluorine-doped SnO2 (FTO) conductive glass is used as a matrix, FeCl3·6H2O, CO(NH)2 and HCl are dissolved in deionized water, and a precursor α-Fe2O3 nanocolumn is synthesized on the FTO conductive glass by a hydrothermal method.

3. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 1, characterized in that: In the step S2, Co(NO3)2·6H2O, Zn(NO3)2·6H2O and 2-methylimidazole are dissolved in methanol to obtain a Co-based metal organic framework material, which is then calcined in an argon atmosphere to obtain a Co single atom catalyst.

4. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 1, characterized in that: In the step S3, a methane premixed flame is used to rapidly sinter the Co single atom catalyst and the precursor α-Fe2O3 in an ultra-high temperature flame.

5. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 2, characterized in that: The step S1 specifically includes the following steps: S1.1 Cut the FTO glass, clean it with ultrasonic, and dry it; S1.2 remove the residual organic protective layer on the surface of FTO glass; S1.3 Weigh 0.81 g of FeCl3·6H2O and 0.27 g of CON2H4 and dissolve them in 30 mL of deionized water to prepare a mixed solution, and adjust the pH to 1.5 with concentrated hydrochloric acid; S1.4 Cover the non-conductive surface of the cleaned FTO glass with polyimide tape, fix it in a hydrothermal kettle, pour the above mixed solution into it to immerse it, seal it, and place it in a hydrothermal reaction at 110°C for 6 hours; S1.5 After the hydrothermal reaction is completed, the FTO conductive glass is taken out and cleaned with deionized water, then placed in a muffle furnace, annealed at 550°C for 1h, and cooled to room temperature with the furnace to obtain a deep red α-Fe2O3 precursor.

6. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 3, characterized in that: The step S2 specifically includes the following steps: S2.1 Weigh 43.65 mg of cobalt nitrate and 847.84 mg of zinc nitrate and dissolve them in 40 mL of methanol to prepare solution A; S2.2 Weigh 2 g of 2-methylimidazole and dissolve it in 20 mL of methanol to prepare solution B; S2.3 While stirring solution A at a speed of 1000 rpm, quickly pour solution B into solution A, making sure that solution B does not touch the bottle wall, to obtain a mixed solution; S2.4 Stir the mixture for 2 seconds, centrifuge and collect the precipitate; S2.5 The precipitate was washed three times with methanol and dried thoroughly at 60 °C to obtain the Co MOF precursor; S2.6 The obtained Co MOF precursor was placed in a tubular furnace, annealed in an argon atmosphere, heated to 900 °C for 4 h 30 min, then kept warm for 2 h, and naturally cooled to room temperature after the end of the heat preservation to obtain Co SACs.

7. The method for preparing a Co single atom modified α-Fe2O3 nanorod photoanode according to claim 3, characterized in that: The step S3 specifically includes the following steps: S3.1 Mix 10 mg Co SACs, 7.6 mL deionized water, 2.4 mL isopropanol, and 20 uL Nafion solution to prepare a suspension; S3.2 Place the suspension in ice water for 5 min and then disperse it ultrasonically for 20 min; S3.3 Place the α-Fe2O3 nanocolumn precursor horizontally on a tray, add 100uL of the suspension, dry at 70°C for 15min, wash with deionized water, and blow dry with nitrogen; S3.4 Repeat the drip coating and drying process 10 times; S3.5 uses a McKenna burner, with the flow rates of CH4 and air set at 2.22 and 17.58 SLPM, and the fuel-to-oxygen equivalence ratio at 1.2; S3.6 The α-Fe2O3 nanocolumn precursor coated with Co SACs was rapidly annealed in an oxygen-deficient flame zone at 1000°C for 30s to finally obtain the Co SACs / α-Fe2O3 photoanode.

8. A Co single atom modified α-Fe2O3 nanorod photoanode, characterized in that: The nanorod photoanode is a Co SACs / α-Fe2O3 photoanode, which is prepared by the preparation method described in any one of claims 1 to 7.

9. Use of a Co single atom modified α-Fe2O3 nanorod photoanode as claimed in claim 8 in photoelectrocatalytic ammonia oxidation.

10. Use of a Co single atom modified α-Fe2O3 nanorod photoanode as claimed in claim 8 in the degradation of ammonia nitrogen pollutants.

Citation Information

Cited By

  • Photoelectric cathode catalyst and electrode preparation method and application thereof

    CN121588839A